A 90‐day preclinical toxicological evaluation in rats of a highly purified and concentrated mulberry leaf extract - Murbach, Timothy S.; Glávits, Róbert; Endres, John R.; Hirka, Gábor; Pasics Szakonyiné, Ilona (Journal of applied toxicology, 2024)
Mulberry (genus Morus) leaves have long been used as a human food, especially in Asia, and animal feed. More recently, mulberry leaf extracts have been introduced as a convenient way to consume mulberry for non‐nutritional functional effects. Reducose® 5% is an Morus alba leaf extract that has been highly purified and standardized to a content of 5 ± 0.5% 1‐deoxynojirimycin, a naturally present polyhydroxylated piperidine alkaloid analog of D‐glucose. This extract has previously been evaluated in acute and subacute (28‐day) oral toxicity studies in which no adverse effects of the test item were observed in mice or rats, respectively. Due to continued and growing interest in the extract in multinational markets, we have now further investigated potential toxic effects in subchronic (90‐day) oral toxicity study in male and female Han:WIST rats. The test item was administered at doses of 850, 1700, and 2550 mg/kg bw/day, and did not cause adverse effects in clinical signs, body weight development, clinical pathology, gross pathology, or histopathology in comparison to the vehicle‐control group. The no‐observed‐adverse‐effect‐level was determined to be 2550 mg/kg bw/day. These results add to the existing body of both preclinical and clinical work relevant to the safety of the extract and of interest to regulators in various global markets. In recent times, extracts of mulberry leaves, which have long been consumed as food, have gained popularity. We have conducted a 90‐day oral toxicity study in rats of a purified Morus alba leaf extract standardized to contain 5 ± 0.5% 1‐deoxynojirimycin to add to past acute and subacute toxicological evaluations. No adverse effects were observed, and no target organs were identified following administration of 0 (vehicle control), 850, 1700, and 2550 mg/kg bw/day. The NOAEL was determined as 2550 mg/kg bw/day.